Gay, Rural, and Coming Out - Nicholas J. Pace (The Rural Educator, 2018)
This case study details the events surrounding a gay student’s “coming out” in a small, rural high school. Through the eyes and experiences of the student, his teachers, classmates, and  community, we hear the story of how the school and community dealt with an issue they had never before actively considered. Through qualitative interviews, the former high school principal describes reactions and lessons learned as the student made his sexual orientation known, attended prom, and was awarded one of three Matthew Shepard Scholarships given in the state. The unexpected way in which events unfolded in the school and community were nearly as surprising as the revelation of the student’s sexual orientation. The experiences reinforce the importance of school climate, meaningful relationships between students and staff, the sometimes hidden challenges of high school, and provide valuable considerations for all educators.